2014
DOI: 10.1080/09168451.2014.915733
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of oral administration of yeast thioredoxin against gastric mucosal injury

Abstract: Thioredoxin (TRX) is a redox regulating protein which has protective effects against oxidative stress-induced damage to cells and tissues. In this study, we investigated the effects of orally administered TRX derived from edible yeast, Saccharomyces cerevisiae, on gastric mucosa. First, we examined the digestibility of orally administered yeast TRX in mice, and detected yeast TRX in the stomach for 4 h after administration. Next, we investigated the mitigation of gastric mucosal injury after the oral administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In this context, Girard et al, (2010) demonstrated a dose-dependent gastroprotective effect of Saccharomyces boulardii in a rat model of ibuprofeninduced gastric ulcers, by reducing the number of gastric ulcers and the ulcerated surface of the gastric mucosa. Taketani et al, (2014) showed a gastroprotective effect of orally administered thioredoxin derived from the edible yeast Saccharomyces cerevisiae, in an HCl/ ethanol-induced model. Their results brought forward an interesting possibility of promoting wound-healing responses through the administration of this compound.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, Girard et al, (2010) demonstrated a dose-dependent gastroprotective effect of Saccharomyces boulardii in a rat model of ibuprofeninduced gastric ulcers, by reducing the number of gastric ulcers and the ulcerated surface of the gastric mucosa. Taketani et al, (2014) showed a gastroprotective effect of orally administered thioredoxin derived from the edible yeast Saccharomyces cerevisiae, in an HCl/ ethanol-induced model. Their results brought forward an interesting possibility of promoting wound-healing responses through the administration of this compound.…”
Section: Discussionmentioning
confidence: 96%
“…However, no studies have been conducted to investigate how long orally administered TRX remains in the stomach. Taketani et al demonstrated that orally administered TRX derived from yeast, which is commonly used in fermented foods, has a protective effect on the gastric mucosa both in in vitro and in vivo models (water-immersion restraint stress and HCl/ethanol-induced gastric ulcer models) [ 72 ]. DNA microarray analysis revealed the upregulation of genes related to tissue repair in ulcer regions of rats administered with yeast TRX.…”
Section: Oral Delivery Of Trxmentioning
confidence: 99%
“…Yeast, such as Saccharomyces boulardii , has been reported to have potential in the treatment and prevention of gastric ulcer induced by ibuprofen in rats ( 51 ). More recently, it was demonstrated using DNA microarray that thioredoxin derived from edible yeast, Saccharomyces cerevisiae , can protect the gastric mucosa by up- or downregulating hundreds of genes involved in the healing of the ulcerative mucosa induced by stress or HCl/ethanol in rats ( 164 ).…”
Section: Prophylactic and Therapeutic Effects Of Probiotics In Gastrimentioning
confidence: 99%